Nonlinear modal aeroservoelastic analysis framework for flexible aircraft - Wang,Y; wynn,A; Palacios,R (AIAA Journal: devoted to aerospace research and development, 2016)
A nonlinear formulation in modal coordinates of the equations of motion of a flexible aircraft is presented. It relies on the projection of the intrinsic equations of geometrically nonlinear composite beams on the linear normal modes at a reference condition, which are coupled with two-dimensional unsteady aerodynamics. The resulting description is suitable for nonlinear dynamic analysis and control design, whereas the description in modal coordinates links directly to linear aeroservoelastic analysis methods. Results are presented on and compared to cantilever wings and full aircraft configurations previously studied in the literature. Linear H∞H∞ control synthesis and closed-loop nonlinear simulations are finally explored on a highly flexible flying wing under large-amplitude discrete gusts. Results show the ability of the proposed framework to capture the nonlinear dynamics of the aeroelastic system, while providing a seamless integration with linear methods, as well as its strength in identification of the dominant contributors to the nonlinear response.